PENGEMBANGAN PRODUK DAN DIGITALISASI PEMASARAN PADA USAHA KECIL OBAT TRADISIONAL (UKOT) PJ PUCUK SIRIH ASAL BANJARMASIN - Anna Khumaira Sari; Muhammad Ikhwan Rizki; Fadlillaturahmah Fadlillaturahmah; Amalia Khairunnisa khairunnisa; Muhammad Rusydi Taufik; Devi Eka Pratama; Akhsanul Rahmatullah Rahmatullah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
South Kalimantan is a wetland area that has a high level of biodiversity, both plants and animals, which can be used as raw materials for herbal products. The herbal medicine company Pucuk Sirih is a Traditional Medicine Small Business which is located in selling various herbal products. PJ Pucuk Sirih wants to develop and innovate products, packaging and marketing systems because since the first production there has been no change in product, packaging and marketing system development. The new product formula, namely Harbumin Capsules (haruan fish capsules) has not yet produced good product quality, this is indicated by the wet capsule products after the production process so it is necessary to evaluate the product formula. The purpose of this community service is to provide training on production and packaging methods in accordance with CPOTB, evaluate the Harbumin capsule formula, produce a digitalized marketing system with website development. The result of the activity is that the production team gains knowledge regarding good production and packaging methods, the results of the evaluation of Harbumin capsule products show that the capsules have met the requirements, the marketing and sales system has been digitized and can be obtained online